2012
DOI: 10.1021/jp208097c
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Relevant Lyotropic Liquid Crystalline Phases in Mixtures of n-Octyl β-d-Glucoside and Water. Determination of the Phase Diagram by Fluorescence Spectroscopy

Abstract: When mixed with water, n-octyl-β-D-glucoside forms self-assembled nanostructures, several of which are liquid crystalline and all of which depend on the water/glucoside ratio and temperature. For practical use of these phases, a detailed understanding of the conditions under which they exist (i.e., the isobaric phase diagram) is required. We use the fluorescence of the dye molecule prodan as a new approach to probe the phases formed in these mixtures. The prodan fluorescence signal depends on the polarity of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 20 publications
4
23
1
Order By: Relevance
“…Prodan dissolved in octylglucoside aggregates has been shown previously to fluoresce at a λ max of ~500 nm with its corresponding emission in a lamellar phase at a much lower wavelength. 22 Prodan in mRL micelles fluoresces at a λ max of ~500 nm while prodan in the mRL lamellar phase emits at the much lower wavelength of ~445 nm. At pH 8.0, prodan emission is more intense with increasing mRL concentration with the λ max shifting from that of free prodan dissolved in water (525 nm) to prodan dissolved in micelles (500 nm) as the concentration increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prodan dissolved in octylglucoside aggregates has been shown previously to fluoresce at a λ max of ~500 nm with its corresponding emission in a lamellar phase at a much lower wavelength. 22 Prodan in mRL micelles fluoresces at a λ max of ~500 nm while prodan in the mRL lamellar phase emits at the much lower wavelength of ~445 nm. At pH 8.0, prodan emission is more intense with increasing mRL concentration with the λ max shifting from that of free prodan dissolved in water (525 nm) to prodan dissolved in micelles (500 nm) as the concentration increases.…”
Section: Resultsmentioning
confidence: 99%
“…Both probes are known to partition into hydrophobic regions of surfactant aggregates, 21,51,52 and their emission intensities or wavelength maxima ( λ max ) depend sensitively on polarity of the aggregate microenvironment. 22 Prodan exhibits a blue-shift in λ max from its free solution value of ~525 nm as its environment becomes more nonpolar, with distinct maxima observed for micelle (~500 nm) versus lamellar (~440 nm) aggregate types. 21 In addition, a common measure of microenvironment polarity is the intensity ratio of the third (III) to first (I) vibronic bands of pyrene; this ratio ranges from values >1 in more nonpolar environments to ~0.5 in extremely polar environments.…”
Section: Resultsmentioning
confidence: 99%
“…Karukstis et al have reported that the Q phase solely existed in a very narrow composition region, and that most of the composition exist as the coexisting region with H or Lα phases. 7) These observations explain why we did not observe the optically isotropic Q phase. On the basis of these results, we concluded that the β-OGlu assembly formed the lyotropic liquid crystalline phases during the solidification and melting of eutectic (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…9) Under ambient atmosphere, β-OGlu forms an isotropic micelle solution (I) and lyotropic liquid crystalline phases composed of hexagonal (H), cubic (Q), and lamellar (Lα) phases in a pure water system, depending on the hydration circumstance of its sugar moiety. [6][7][8] In our previous study, 10) lyotropic phase transitions of liquid crystalline phases were observed due to the change of the concentration of β-OGlu during the ice freezing and thawing processes. Specific ice crystal growth from spherical to a hexagonal symmetry was recognized in the micelle solution.…”
mentioning
confidence: 96%
See 1 more Smart Citation